Pengaruh Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah dan Tax Planing Terhadap Kualitas Laporan Keuangan (Studi Kasus UMKM di kota Yogyakarta) - Ayem, Sri; Prihatin, Risma (Jurnal Akuntansi Profesi, 2020)
The purpose of this research is to describe (1) the influence of small and medium microfinance accounting standard variables (SAK-EMKM) on the quality of MSME financial reports, (2) the effect of Tax Planing on the quality of UMKM financial statements in the city of Yogyakarta. This research is classified as a type of quantitative research. The population is all MSMEs. In this study, small and medium micro businesses in the city of Yogyakarta numbered 106 respondents. The data conclusion method uses questionnaire, while the data analysis technique uses multiple regression analysis supported by t test (partial test), F test (F-test), R2 test (coefficient of determination) and classic assumption test consisting of normality test, test multicollinity, heteroscedasticity test, and linearity test. The results showed that the multiple linear regression equation for two predictors Y = 7.749 + 0.327 X1 + 0.082 X2, meaning that the application of SAK-EMKM, Tax Planing contributed greatly to the quality of financial reports. The magnitude of the effect seen from the coefficient of determination (R2). Detremination coefficient value is 0.821. The results of the coefficient of determination show that the application of SAK-EMKM and Tax Planing has a positive influence on the quality of financial statements of 81.2% and the remaining 17.9% is influenced by other variables.